Mesenteric ischemia-reperfusion: an overview of preclinical drug strategies. Issue 7 (July 2018) - Bertoni, Simona; Ballabeni, Vigilio; Barocelli, Elisabetta; Tognolini, Massimiliano
Highlights: Mesenteric ischemia-reperfusion is a rare event with high mortality. A multitude of drug strategies were proposed in preclinical studies. Further investigations are needed to identify an efficacious clinical approach. Timely administration of multitarget agents can be crucial for effective drug therapy. Abstract : Mesenteric ischemia is a surgical emergency caused by a transient reduction in blood perfusion to the bowel. Despite accounting for only 0.1% of hospital admissions and 1–2% of gastrointestinal diseases, its elusive symptoms often lead to dramatically high morbidity and mortality rates. The complex cascade of inflammatory events and mediators triggered by mesenteric ischemia-reperfusion (I/R) accounts for the plethora of proposed pharmacological targets and for the current lack of an efficacious drug strategy for its management. It is hoped that a deeper understanding of its pathogenesis and the preclinical therapeutic strategies identified to date and described herein will improve the translation into the clinical setting of the pharmacological armamentarium against a life-threatening disorder that is currently mainly managed surgically.